Psychological well-being as a moderator in the relationship of school culture, workload, work stress and job satisfaction among middle leaders primary school Putrajaya - Yazid, Nurhanani; Abd. Aziz, Mohd Faiq; Musa, Siti Nur Syuhada (Human Resource Management Academic Research Society, 2023)
The issue of job satisfaction among middle leaders in Malaysia is not a new thing in the current education context. However, studies on job satisfaction and even the factors that affect job satisfaction, especially among middle leaders in primary schools, have not been done before. Therefore, this study aims to study in depth to identify the level and relationship, examine the main contributing factors to job satisfaction and see the role of the existence of psychological well-being as a moderator in the relationship between school culture, workload, stress and job satisfaction among middle school leaders low. Quantitative survey research using a self-administered questionnaire was conducted online involving 196 respondents consisting of Putrajaya primary school middle leaders. Descriptive and inference statistical analysis is used such as the Pearson Correlation Test, Multiple Regression Analysis and tests that test moderation using the PROCESS Hayes Model 1 Macro. It is also recommended that further research be conducted to explore and understand more deeply the role that psychological well-being plays in improving the relationship between school culture, workload, work stress and job satisfaction among middle leaders from various different angles to ensure its effectiveness.